Determination of Glutathione, Selenium, and Malondialdehyde in Different Edible Mushroom Species - Dogan, Hacer; Coteli, Ebru; Karatas, Fikret (Humana Press Inc, 2016)
In this study, the amount of reduced glutathione (GSH), oxidized glutathione (GSSG), and malondialdehyde (MDA) were determined by high performance liquid chromatography (HPLC), and selenium was determined by using the fluorescence spectrophotometer in eight different species of edible mushrooms. Brittlegill mushroom (Russula delica), meadow mushroom (Agaricus campestris), dryad's saddle mushroom (Polyporus squamosus), white button mushroom (Agaricus bisporus), Pleurotus spp., ink mushroom (Coprinus atramentarius), ebekari mushroom (slimy) (ElazA +/- g local) and dagger aAYA +/- r mushroom (Pleurotus eryngii) (Tunceli local) were used for analysis. The amounts of GSH, GSSG, Se, and MDA with GSH/GSSG ratio in the eight different species of edible mushrooms were observed in between 269.10 +/- 16.94-1554.83 +/- 58.12 mu g/g; 23.55 +/- 1.89-841.90 +/- 20.03 mu g/g; 15.06 +/- 1.56-82.10 +/- 3.84 mu g/g; 5.46 +/- 0.50-27.45 +/- 2.58 mu g/g wet weight and 0.32-41.35, respectively. There is a weak correlation (R (2) = 0.389) between MDA and Se, on the other hand, the correlation (R (2) = 0.831) between GSH/GSSG ratio and selenium in mushrooms are reasonable well. In a similar manner, there is a weak correlation (R (2) = 0551) between GSH/GSSG and MDA ratios in mushrooms. It was found that these edible mushroom species are good source of glutathione (GSH, GSSG), and selenium (Se) in terms of quantities obtained; therefore, it can be said that mushrooms are a rich source of antioxidants.
Keywords: Mushrooms; Glutathione; Selenium; Malondialdehyde